2006
DOI: 10.1016/s0022-5347(05)00033-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Clinical Fractures After Gonadotropin-Releasing Hormone Agonist Therapy for Prostate Cancer

Abstract: GnRH agonists increase the risk of clinical fracture in men with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(71 citation statements)
references
References 14 publications
3
65
0
3
Order By: Relevance
“…Previous studies, including analysis of the present dataset [12], have shown an increased occurrence of fractures in patients with prostate cancer treated with androgen deprivation [45][46][47][48][49]. We also found a slightly increased risk of all (including hip) fractures in patients on insulin, also classified as tentative.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies, including analysis of the present dataset [12], have shown an increased occurrence of fractures in patients with prostate cancer treated with androgen deprivation [45][46][47][48][49]. We also found a slightly increased risk of all (including hip) fractures in patients on insulin, also classified as tentative.…”
Section: Discussionsupporting
confidence: 71%
“…Patients with at least nine treatments within the first year were 62% more likely to suffer a fragility fracture [35].…”
Section: Osteoporosis Secondary To Antiandrogen Therapy For Prostate mentioning
confidence: 99%
“…One important cause of osteoporosis in adult men is androgen deprivation or withdrawal therapy (ADT) for prostate cancer. Men who are treated by orchiectomy or with analogs of gonadotropin-releasing hormone to suppress the pituitary and/or with androgen-receptor-blocking agents are at high risk for bone loss, osteoporosis, and fracture [2][3][4][5]. In a retrospective 4-year study of 288 men undergoing androgen deprivation therapy, Lopez et al [6] reported that the incidence of peripheral fractures was 1.9 per 100 patient-years in the men undergoing ADT compared to 0.5 in a large control group.…”
Section: Introductionmentioning
confidence: 99%